2018
DOI: 10.1016/j.redox.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Age-related oxidative changes in pancreatic islets are predominantly located in the vascular system

Abstract: Aged tissues usually show a decreased regenerative capacity accompanied by a decline in functionality. During aging pancreatic islets also undergo several morphological and metabolic changes. Besides proliferative and regenerative limitations, endocrine cells lose their secretory capacity, contributing to a decline in functional islet mass and a deregulated glucose homeostasis. This is linked to several features of aging, such as induction of cellular senescence or the formation of modified proteins, such as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 72 publications
1
25
1
Order By: Relevance
“…For immunohistochemical and immunofluorescent analysis, longitudinal, serial sections (2 μm) of young and aged mice before and after 2 as well as 21 days of the +CH intervention were processed as previously described [ 19 ]. Pancreatic tissue slices were incubated with primary antibodies against rabbit Ki67 (1:1000, Abcam, Cambridge, UK) and mouse caspase-3 (1:100, Life Technologies, Darmstadt, Germany) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For immunohistochemical and immunofluorescent analysis, longitudinal, serial sections (2 μm) of young and aged mice before and after 2 as well as 21 days of the +CH intervention were processed as previously described [ 19 ]. Pancreatic tissue slices were incubated with primary antibodies against rabbit Ki67 (1:1000, Abcam, Cambridge, UK) and mouse caspase-3 (1:100, Life Technologies, Darmstadt, Germany) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Besides dietary factors, aging and related alterations have been shown to influence beta-cell characteristics. Recently, we demonstrated that pancreatic islets of normoglycemic wild-type mice progressively lose their proliferative and regenerative potential, associated with the induction of cellular senescence, known to induce an irreversible cell cycle arrest [ 19 ]. Furthermore, different well-known hallmarks of aging, such as mitochondrial dysfunction, elevated oxidative stress and inflammation, all linked to a dysregulated redox balance, affect beta-cells by impairing their secretory function and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical labeling and quantitative analysis was performed as previously described 15 . A list of used antibodies and applied concentrations are provided as supplementary information (SI Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The previous studies suggested the β cell dysfunction with age is mainly caused by the loss of functional β cell mass. However, in recent years, some researchers have put forward different opinions, suggesting that the intrinsic function of β cells does not significantly change with age, but their fully functioning is affected by the systemic senescent environment [ 68 , 69 ].…”
Section: Aging and Diabetesmentioning
confidence: 99%